Risk Factors and Imaging Mechanisms of Fatigue After Mild Ischemic Stroke: An Exploratory Study From a Single Chinese Center - Zhang, Xiaoxiao; Fang, Hongjuan; Ma, Ding; Duan, Yunyun; Wang, Zhaozhao; Zhang, Ning; Wang, Chunxue (Frontiers in Neurology, 2021)
Objective To explore the biochemical risk factors and imaging mechanisms of post fatigue after mild ischemic stroke among a Chinese population. Methods Fourty consecutive patients with mild ischemic stroke within onset of 14 ± 2 days were enrolled between March and June 2018. The clinical information, scale data, biomarkers in peripheral venous blood and imaging data during hospitalization and follow-up period were collected. Results Patient age (range 34 to 78) was positively correlated with the prevalence of fatigue (p=0.009). Both blood norepinephrine and serotonin levels during hospitalization were negatively correlated to the prevalence of post-stroke fatigue (model 1 p=0.009 and model 2 P=0.043, respectively). Infarct of right cerebral hemisphere is positively correlated with the occurrence of fatigue after mild ischemic stroke (p=0.020). Compared to non-fatigue patients, amplitude of low-frequency fluctuation (ALFF) were lower in several areas of brain in stroke patients with fatigue, including the right orbital inferior frontal, right inner orbital frontal, right frontal, right triangular frontal inferior, right anterior and lateral cingulate, and right medial frontal gyruses. Analysis of the difference in functional connectivity between the fatigue and non-fatigue groups found no cluster. Conclusions Frontal lobe-related neural pathways may play an essential role in the regulation of fatigue after mild ischemic stroke. Abnormal neural circuits may reduce the levels of neurotransmitters such as serotonin and norepinephrine and lead to post-stroke fatigue.